Social Media, Innovation, and Digital Literature towards Digital Business Strategy - Ade Saputra, Guntur; Hapzi Ali (Dinasti Publisher, 2024)
This research aims to explore the influence of social media on digital business strategy. The research methodology used is literature research which involves exploration, evaluation and systematic analysis of relevant literature from various scientific sources. The choice of this method is based on its ability to provide a comprehensive approach to understanding social media in the context of digital business strategy. Research findings show that social media has a significant influence on digital business strategy. The use of social media can help companies build a strong brand, increase interaction with customers, and expand market reach. Apart from that, innovation also has an important role in digital business strategy. Companies that are able to innovate continuously can face challenges and opportunities in a rapidly changing business environment. This research concludes that the influence of social media, innovation and digital literature on digital business strategy is very significant. To develop adaptive and innovative business strategies in the era of digital transformation, it is important to understand and make good use of social media, continue to encourage innovation, and use digital literature as a source of insight and knowledge